VO#053 Quotation for additional work in lecture theatre rev.00 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the quotation for for additional work in lecture theatre of BRACU new campus project.